In-situ fibrillated polytetrafluoroethylene (PTFE) in thermoplastic polyurethane (TPU) via melt blending: Effect on rheological behavior, mechanical properties, and microcellular foamability. (3rd January 2018) - Huang, An; Peng, Xiangfang; Turng, Lih-Sheng
Abstract: An approach to produce in situ fibrillated polytetrafluoroethylene (PTFE) in thermoplastic polyurethane (TPU) has been developed and the effect on the rheological behavior, mechanical properties, and microcellular foamability of TPU/PTFE composites has been studied. A drastic transformation of oval or rounded PTFE particles into highly stretched, sub-micron fibrils in the TPU matrix via melt compounding was revealed by scanning electron microscopy (SEM) images. Dynamic mechanical analysis (DMA) and tensile tests showed substantial improvements in the measured properties of the TPU/PTFE composites. The oscillatory shear behavior of the TPU/PTFE composites in the linear viscoelastic region was studied. Dynamic frequency sweep experiments revealed that the storage modulus ( G′ ) increased and the slope of G′ vs. frequency decreased at low frequencies compared to neat TPU. This indicated that the entangled fibril structure responded elastically. Microcellular injection foaming (MIF) trials, SEM, and micro-computed tomography (Micro-CT) confirmed that the presence of PTFE fibrils dramatically improved the foamed structure, resulting in a two-order-increase in pore density (cell density) in comparison with neat TPU. Moreover, the fibrillar PTFE dramatically enhanced the hydrophobicity and decreased the coefficient of friction of the TPU/PTFE composites. Graphical abstract: Image 1 Highlights: First study on TPU/PTFE composites and foams by twin-screw extruder and microcellular injection molding. Only a few papers have reported in situ polymer–polymer fibrillar composites (ispp-FCs) made by melt compounding. PTFE underwent fibrillation and deformed into a fibrillar structure with a large aspect ratio from original oval shape. The viscoelastic properties (e.g., frequency sweeps, creep and stress relaxation) and the foamability have been studied. The hydrophilic and tribological properties have been investigated with aims to broaden the application of TPU.